On Intergenerational Risk Sharing within Social Security Schemes - Andreas Wagener (Center for Economic Studies and ifo Institute (CESifo), 2001)
One of the main reasons to include pay-as-you-go (PAYG) schemes in multi-pillared pension systems is that they may entail beneficial risk-sharing and diversification features However, depending on the pension formula these features vary significantly for different types of PAYG schemes. We derive individually most-preferred PAYG rules (represented by a risk-sharing parameter) for young and old members of a society. These preferences depend among others on the correlation between the risks of PAYG scheme and funded schemes and on the trust in the durability of the pension rule. We find that the generations' interests with respect to the optimal PAYG policy need not necessarily clash, in particular not if future economic conditions are expected to be similar to today's. We discuss the implications of these findings for the political economy of multi-pillar pension systems.
Keywords: 330; Social security; intergenerational risk sharing; pay-as-you-go pensions; majority voting